ANALISIS YURIDIS TENTANG RUJUK DALAM TENGGANG MASA ‘IDDAH TALAK RAJ’I MENURUT UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN DAN HUKUM ISLAM - MUHAMMAD ICHSAN PARINDURI (PREMISE LAW JURNAL, 2016)
A marriage is a contract or an agreement to allow a biological relationship between a man and a woman in order to realize a happy family life covered with peace, love, and affection blessed by the God Almighty. The research method is a judicial normative; a library legal research, namely analyzing the existed library materials with the historical and statute approaches, and the vertical and horizontal synchronizations in Indonesian positive laws. From the research on talaq raj'i and iddah stipulated in the Islamic system of jurisprudence and Compilation of Islamic Law son marriage, it is found out that talaq is classified into Talaq Sunni, Thalaq Bidi 'i, Thalaq neither Sunnin or Bidi 7.  If her husband insists on remarrying her, the remarriage can be implemented by the ruling of the Religious Court. The legal consequences of implementation of remarriage during Iddah Talak Raj'i, her husband gives some alimony, maskan and kiswah to his former wife, with the exception, his former wife has been imposed talak ba 'in or nusyuz.   Keywords: Remarriage, Iddah Period, Talaq Raj'i, Compilation of Islamic Law, and Islamic System of Jurisprudence